Ant Species Inventory Based on Habitat Fragmentation in the Pangandaran Nature Reserve - Sinta Aisia; Azzumi Azka Gigannia; Wila Fitria; Sukma Nur Izzati; Meiry Fadilah Noor (Program Studi Pendidikan Biologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kuningan, 2026)
Ants are social insects that play a vital role in maintaining ecosystem balance and can serve as ecological indicators of environmental change. This study aimed to determine the variation of ant species in habitats with varying levels of disturbance. Data collection methods included pitfall traps and bait traps at three different locations over two days. Data analysis was performed by calculating the Shannon-Wiener diversity index and observing species composition and abundance. The results showed that 7,350 individual ants were identified in five subfamilies and eleven genera. The genus Anoplolepis was the most dominant in this study. The diversity index value was moderate in more protected areas and low in more disturbed areas. Community diversity was influenced by several environmental parameters such as temperature, light intensity, and humidity. The results also showed that ant preferences for protein and carbohydrate baits varied across genera. In conclusion, the level of habitat disturbance influences the composition and structure of ant communities, which can be used as a basis for monitoring ecosystem conditions.